2017
DOI: 10.3390/ijerph14060556
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Chronic Arsenic Exposure on Adverse Pregnancy Outcomes

Abstract: Exposure to arsenic has a number of known detrimental health effects but impact on pregnancy outcomes is not as widely recognized. This narrative review examines existing epidemiological evidence investigating the association between arsenic exposure via drinking water and adverse pregnancy outcomes. We reviewed published epidemiological studies from around the world on impact of chronic arsenic exposure on spontaneous abortion, stillbirth, neonatal death, post neonatal death, low birth weight and preterm baby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 34 publications
3
43
2
Order By: Relevance
“…However, our GM As concentrations (9.52 μg/L) were lower than what was reported among pregnant women in the LIFESTAGES cohort, in Boston (15.0 μg/L). Prenatal exposure to As in drinking water has been previously associated with spontaneous abortion, low birth weight, and still birth, primarily in developing countries, such as Bangladesh, with endemic As contamination (Milton et al 2017;Mohammed-Abdul et al 2015). While the association between urinary As and reproductive and perinatal health outcomes among women in the USA has not been fully explored, Davis et al (2015) did report negative associations between maternal urinary As concentrations (at levels lower than observed in our population) and reduced fetal head circumference.…”
Section: Discussioncontrasting
confidence: 55%
“…However, our GM As concentrations (9.52 μg/L) were lower than what was reported among pregnant women in the LIFESTAGES cohort, in Boston (15.0 μg/L). Prenatal exposure to As in drinking water has been previously associated with spontaneous abortion, low birth weight, and still birth, primarily in developing countries, such as Bangladesh, with endemic As contamination (Milton et al 2017;Mohammed-Abdul et al 2015). While the association between urinary As and reproductive and perinatal health outcomes among women in the USA has not been fully explored, Davis et al (2015) did report negative associations between maternal urinary As concentrations (at levels lower than observed in our population) and reduced fetal head circumference.…”
Section: Discussioncontrasting
confidence: 55%
“…2). Furthermore, this element may pass through the placenta, increasing rates of spontaneous abortion, low birth weights, and several other conditions (Hopenhayn et al 2003;Milton et al 2017).…”
Section: A Brief Overview Of Global Arsenic Exposure and Population-lmentioning
confidence: 99%
“…For example, in our study arsenic, cadmium, chromium and lead all were all highly enriched with SA genes. Consistent with these results, multiple meta-analyses of epidemiological literature have concluded that high levels of arsenic exposure (>50 ppb) are associated with SA and that plausible mechanisms exist for arsenic causing SA due to its endocrine disrupting properties (Milton et al 2017; Rahman et al 2016). A recent report showed lead levels in the hair of pregnant woman were associated with risk of missed abortion (i.e., loss of pregnancy with retention of products of conception) (Zhao et al 2017).…”
Section: Discussionmentioning
confidence: 64%